Upgrading Posyandu Elderly Services in Early Detection of Degenerative Diseases in Posyandu Elderly in Pasir Lor Village, Karanglewas District, Banyumas - Sumarni; Dyah Puji Astuti; Fitria Prabandari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Degenerative disease is a disorder in which there is a gradual decline in function or damage to the structure of the body. The services provided at the elderly Posyandu are still limited to checking blood pressure, weighing, providing additional food and health education, but early detection of degenerative diseases has not been carried out, such as heart by checking cholesterol, DM by checking blood sugar levels, and detecting joint disease by checking uric acid levels. The activity method consists of preparation, implementation and evaluation. Preparatory activities are carried out for coordination with partners and preparation of all activity needs. Implementation activities consist of two activities, namely counseling and training on early detection of degenerative diseases. Evaluation is carried out to determine the effectiveness of the implementation of community service activities that have been carried out. The results showed that most of the knowledge of health cadres before counseling had poor knowledge, namely 69.8%, while 23.3% had quite good knowledge and 2.3% already had good knowledge about degenerative diseases. Meanwhile, after counseling, most of the cadres had good knowledge, namely 80.5%. while 19.5% knowledge is quite good. the ability of cadres in early detection through blood tests most of the cadres already have good skills at 88% while 12% are in the sufficient category. The conclusion of this activity is that some cadres have good knowledge and skills after upgrading cadres in early detection of degenerative diseases in the elderly, so this activity is very important to improve the quality of services for the elderly posyandu